Editorial: Rethinking Anti-Trafficking Funding: Following the money, again - Sharapov, Kiril; Hoff, Suzanne; Mendel, Jonathan; Gerasimov, Borislav (Anti-Trafficking Review, 2024)
This Editorial introduces a special issue of the Anti-Trafficking Review that investigates where the funding for anti-trafficking work comes from, goes to, and with what effect. It reflects on some of the changes in funding that have occurred over the past ten years and why it is necessary to research and analyse these changes. It then introduces the articles in the special issue and concludes with suggestions for future research on the topic.